Evidence for a seasonally dependent ring plasma in the region between Saturn's A Ring and Enceladus' orbit. Issue 8 (17th August 2015) - Persoon, A. M.; Gurnett, D. A.; Kurth, W. S.; Groene, J. B.; Faden, J. B.
Abstract Equatorial electron density measurements from the Cassini Radio and Plasma Wave Science experiment are derived from the upper hybrid resonance frequency from Saturn Orbit Insertion (SOI) on 1 July 2004 through 21 May 2013. These densities are used to determine the characteristics of the plasma in the inner magnetosphere of Saturn between the outer edge of the A Ring and the orbit of Enceladus. Electron densities obtained when Cassini first arrived at Saturn on 1 July 2004 showed a plasma distribution decreasing radially outward from Saturn in the direction of Enceladus, the expected distribution of a centrifugally driven plasma expanding radially outward from a source in the main rings. We examine equatorial electron densities in the region between 2.4 and 4.0 Rs and show that the density measurements in this region exhibit a strong seasonal dependence resulting from photon‐induced decomposition of icy particles on the ring surfaces, a decomposition process which is controlled by the solar incidence angle. This seasonal dependence will have plasma density implications for Cassini when the spacecraft returns to the region just beyond the A Ring in 2016.